Comparison of Rifabutin-Based Versus Rifampin-Based Regimens for the Treatment of Mycobacterium avium Complex: A meta-Analysis Study - Bahareh Hajikhani; Mohammad Javad Nasiri; Brian C. Adkinson; Taher Azimi; Farima Khalili; Mehdi Goudarzi; Masoud Dadashi; Masoud Dadashi; Mukunthan Murthi; Mehdi Mirsaeidi (Frontiers Media S.A., 2021)
Background: The incidence of Mycobacterium avium complex (MAC) increases as immunosuppressed conditions become more common. MAC's standard treatment regimen includes a macrolide, ethambutol, and a rifamycin, among which rifampin and rifabutin are the most commonly used. Although current guidelines recommend initial therapy for MAC with rifampin, it has been theorized to be less efficacious than rifabutin.Methods: We reviewed the relevant scientific literature published up to February 18, 2020. Statistical analyses were performed with Comprehensive Meta-Analysis Software Version 2.0 (Biostat, Englewood, NJ). The pooled frequency with 95% confidence intervals (CI) was assessed using a random-effect model. We considered P <0.05 as statistically significant for publication bias.Results: After reviewing 3665 records, we identified 24 studies that satisfied the inclusion criteria. Among these studies, 8 had rifabutin in their regimens (rifabutin group) and 16 had rifampin in their regimens (rifampin group). The estimated pooled treatment success rate was found to be 54.7% (95% CI 41.0-67.0%) in rifabutin groups and 67.5% (95% CI 55.7-77.4%) in rifampin groups. There was no evidence of publication bias among the included studies (Egger's test p-value was 0.7).Conclusion: In this study, it was shown that in comparison to Rifabutin, rifampin has similar treatment success rates in treating MAC. In order to determine the exact preference of each of these drugs, double-blind clinical trial studies are recommended.